Unpolished Thai rice prevents ACF formation and dysplastic progression in AOM-induced rats and induces apoptosis through redox alteration in CaCo-2 cells - Achiraya Tammasakchai (2018)
Oxidative stress is associated with colon carcinogenesis including aberrant crypt foci (ACF) formation and it plays an important role in pathophysiological changes in cancer cells. The aims of this study were to investigate the effects of dietary unpolished Thai rice (UTR) on ACF formation and dysplastic progression in azoxymethane (AOM)-treated rats. Anti-cancer efficacy of UTR regarding apoptotic induction and oxidative redox status in human colon cancer (CaCo-2) cells was also investigated. Rats given 20% and 70% of UTR in the diet showed significantly and dose-dependently decreased total number of ACF. UTR treatment also was strongly associated with the low percentage of dysplastic progression and mucin depletion. In addition, we found that UTR significantly induced cancer cell apoptosis, increased cellular oxidants, and decreased the level of GSH/GSSG ratio in CaCo-2 cells. Our study suggests that UTR supplementation may be a useful strategy for CRC prevention with the inhibition of precancerous progression, with induction of cancer cell apoptosis through redox alteration.